Beta-alanine supplementation improves time to exhaustion, but not aerobic capacity, in competitive middle- and long-distance runners - David Marko; Ronald L. Snarr; Petr Bahenský; Václav Bunc; Miroslav Krajcigr; Tomáš Malý (Journal of the International Society of Sports Nutrition)
Background Beta-alanine (βA) is a non-essential amino acid purportedly used to enhance aerobic exercise performance. While previous research indicates the benefits of βA on time to exhaustion (TTE) and aerobic capacity (VO2peak) in adults, evidence is lacking in adolescent athletes. Thus, the purpose of this study was to determine the effects of 4 weeks of βA supplementation on aerobic performance in adolescent runners.Methods Twenty-seven middle- and long-distance runners (aged 17.36 ± 2.17 years) were randomly divided into a βA or placebo (PL) group (maltodextrin). Subjects performed maximal graded exercise tests (GXT) and submaximal trials (SMT; 80% of VO2peak for 1500 m) on a treadmill before and after 14 and 28 days of supplementation or PL. Respiratory (VE) metabolic (VO2, RER, lactate [La]), and cardiovascular (HR) variables were measured during the GXT and SMT, along with the first (VT1) and second ventilatory threshold (VT2) and TTE monitored during the GXT only. Within- and between-group differences were assessed using a repeated-measures mixed-model analysis of variance.Results Findings indicated that despite a trivial increase in VO2peak over 4 weeks, the βA group increased TTE by 6.5% compared to 1.4% in the PL group (d = 0.46). Additionally, small effects in HRmax, VE, [La], and TTE were observed between groups favoring βA. Regarding the SMT, both average HR and RER decreased by 4% in the βA group, with no changes for the PL.Conclusions Despite no evidence to suggest increases in VO2peak, practitioners should note that improvements in TTE may be observed after 28 days of βA supplementation in adolescent runners.